Family Leisure as a Context to Support Augmentative and Alternative Communication Intervention for Young Children with Complex Communication Needs - O'Neill, Tara; Mandak, Kelsey; Wilkinson, Krista M. (Seminars in Speech and Language, 2017)
Families are often the most significant communication partners for children who require augmentative and alternative communication (AAC). Because family-centered approaches are recommended practice in speech-language pathology, a primary role for speech-language pathologists (SLPs) serving children who require AAC is to support families in integrating communication into highly valued, existing family activities. Family leisure activities can provide a naturally supportive context for AAC, because they provide multiple opportunities for children to interact and practice using AAC with natural communication partners. This article aims to guide SLPs in utilizing family leisure as a context for AAC intervention. We describe the benefits and constraints of engaging in leisure for families with children with disabilities. We define family leisure, which includes two distinct types of leisure activities: core and balance. Finally, we provide a case example of a family that highlights the integration of AAC into both types of leisure activities.
Keywords: Augmentative and alternative communication; family leisure; family-centered practice